Establishment of the human cardiac models using gene editing and reprogramming in Human Pluripotent Stem Cells to understand the putative functions of the G-protein coupled receptor kinase 5 polymorphism (GRK5-L41) - Hoang, Minh Duc (2017)
A nonsynonymous single polymorphism (SNP) in G protein-coupled receptor kinase 5 (GRK5) was discovered in 2008 that changes the amino acid at the position 41 from Glutamine (Q) into Leucine (L) (Liggett et al., 2008). The putative functions of the GRK5-L41 polymorphism were reported to be involved in faster desensitisation of both b1 and b2 adrenergic receptors in vitro and the cardiac protective functions by improving the survival rate of patients with heart failure conditions or transplantation in vivo. Nevertheless, the mechanisms underlying these processes are still poorly understood, which is the purpose of this thesis.